Nectar robbing in Collaea cipoensis (Fabaceae), an endemic shrub of the Brazilian rupestrian grasslands - Irene Gelvez-Zúñiga; Armando Aguirre; Silvana Martén-Rodríguez; Vanessa Matos-Gomes; Arleu Barbosa; Leandra Bordignon; Rosana Rocha; Geraldo W. Fernandes (Revista Mexicana de Biodiversidad)
Nectar robbery is common in flowering plants with tubular corollas and can affect plant reproductive success. Our study characterized the interaction between potential pollinators and nectar robbers, and assessed the effects on flower abortion in a population of the restricted endemic Collaea cipoensis (Fabaceae) at Serra do Cipó, Brazil. We conducted observations of floral visitors to identify potential pollinators from nectar robbers and described visitor behavior. We also analyzed the frequency of robbery and its relationship with flower visitation. Trigona spinipes and Apis mellifera were identified as the main nectar robbers and two humming bird species Colibri serrirostris and Eupetomena macroura, as potential pollinators. Overall, 570 sampled flowers presented robber damage while 716 were intact. Intact flowers received more visits than flowers with damage. Mean flower abortion ratio did not vary between damaged and intact flowers. Accordingly, a survey of developed fruits indicated that 86% of fruits came from intact flowers. Our results suggest that the damage by nectar robbers in C. cipoensis flowers could affect the reproductive success of this species, interfering with fruit production.